Relationship between arrival timing and breeding success of intra-tropical migratory Fork-tailed Flycatchers (Tyrannus savana) - Bejarano, Vanesa [UNESP]; Jahn, Alex E. [UNESP] (Wiley-Blackwell, 2018)
For migratory birds, early arrival at breeding areas has many benefits, such as acquisition of better territories and mates. This strategy has been found in numerous species breeding at north-temperate latitudes, but has not been yet reported for intra-tropical migratory species. We evaluated the relationship between arrival date, initiation of breeding, and breeding success of Fork-tailed Flycatchers (Tyrannus savana) breeding in southeastern Brazil and overwintering in northern South America. We color-banded adult flycatchers during three breeding seasons and searched for them during the following breeding seasons. We also monitored nests from construction until either failure or fledging of young. We found that: (1) male Fork-tailed Flycatchers arrived at the breeding site earlier than females, (2) males that arrived earlier had greater breeding success, and (3) nests where eggs were laid earlier in the breeding season were more likely to be successful than those where eggs were laid later. Male Fork-tailed Flycatchers appeared to benefit from early arrival at a tropical breeding site, potentially mediated by their ability to acquire a high-quality territory and mate as early as possible, and by the ability of their mate to begin breeding as early as possible. Breeding success for female Fork-tailed Flycatchers may be determined primarily by a combination of the arrival date of their mate and how quickly they can begin breeding. Our results suggest that protandry occurs in an intra-tropical migratory bird and that early arrival of males and early initiation of reproduction by females results in greater reproductive success. A better understanding of the underlying mechanisms that control the timing of migration and reproduction of this and other intra-tropical migratory species is important for evaluating the challenges they face in light of current and future rapid environmental changes.
Keywords: Brazil; Cerrado; protandry; reproduction; South America; spring